Perceived Organizational Support for employee creativity: The mediating role of Knowledge Sharing - Gumelar, Akbar Agus; Fajri, Annisa (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background - Perceived organizational support influences employee commitment, productivity, satisfaction, and intention, this research concentrates on how perceived organizational support affects employee creativity. Research purposes - Examine the relationship between perceived organizational support and employee creativity as mediated by knowledge sharing. Design/ Methodology/ Approach - We report the results of a questionnaire survey of a sample of 139 professional employees working in the IT industry in Semarang. Results and Discussion - Our findings based on path analysis indicate that knowledge sharing mediates the relationship between perceived organizational support and employee creativity. Conclusion - Employees who feel perceived organizational support will encourage more employee knowledge sharing and creativity than employees with low levels of perceived organizational support. Research implications - We contribute to knowledge by proposing an overall theoretical background on organizational support theory and a job demands–resources model by incorporating social exchange theory. Research limitations - This research does not look at it from an organizational perspective; just from an employee's perspective.